An economic analysis of the cost and benefits of S.E.C. rule 12b-1 - Trzcinka, Charles A.; Zweig, Robert; Salomon Brothers Center for the Study of Financial Institutions ([New York] : Salomon Brothers Center for the Study of Financial Institutions, Leonard N. Stern School of Business, New York University, 1990)
This book extracts some of the economic and cost analysis of the U.S. security and exchange commission under the the clause, Rule 12b-1.
Includes bibliographical references (p. 68).
asm; 12/02/19
Loans
Keywords: Mutual funds